PENGELOLAAN FASILITAS DAN INFRASTURKTUR DI SEKOLAH DASAR 101767 TEMBUNG UNTUK MENINGKATKAN PEMBELAJARAN YANG OPTIMAL - Samosir, Berliana; Sihotang, Enjelika Chrismas; Rahmadani, Rahmadani; Manalu, Raiga Yesica; Trihandayani, Trihandayani; Lubis, Wildansyah; Ikhlas, Muhammad; Budianto , Agum (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the management of facilities and infrastructure in primary schools in supporting optimal learning. The research method used is a qualitative approach with data collection techniques in the form of semi-structured interviews, field observations and documentation. The results show that although basic facilities, such as tables, chairs and stationery, are available in adequate conditions, some obstacles remain, such as the limitations of infocus and other technological devices. Teachers creatively overcome these limitations with alternative ways of teaching. This result confirms the importance of sustainable facility management and support from external stakeholders to improve the quality of education. Recommendations include increasing the availability of supporting technology and routine maintenance of facilities to support more effective and interactive learning.